Contemplation & counseling : an integrative model for practitioners - Blanton, P. Gregg (CAPS Books (Christian Association For Psychological Studies), 2019)
Can contemplative prayer be integrated into therapeutic work? Building an alliance between science, theology, and Christian contemplative thought, Gregg Blanton presents a new paradigm for integrating contemplative prayer with counseling practice. This practical resource offers eleven fundamental interventions to fit the needs of clients and a practical four-stage process for helping clients change.